Reproduction of Dioscorea composita - Viana, Ana Maria; Felippe, Gil Martins (Pesquisa Agropecuaria Brasileira, 2014)
The experiments were carried out in Campinas, SP, Brazil, to study seed germination, and the rooting of cuttings of yam (Dioscorea spp.). The cuttings used consisted of leaf blade, petiole, pulvini and 1cm of the plant stem above and under the leaf axil. Rooting was promoted in cuttings by IBA. No rooting occurred in untreated cuttings. Germination was studied with seeds stored from one to eleven months. With storage the seeds lost their sensibility to light. Germination rate was faster with seeds stored for over eight months than for the seeds stored for shorter periods.